Answer:
-1
Step-by-step explanation:
Simply plug in (-1) to both equations and add.
Equation 1:
2(-1)^2 = 2
3(-1) = -3
2 + -3 - 1 = -2
Equation 2:
-( - 1) = 1
Add both together:
-2 + 1 = -1
The equation is 2x² + 3x - 1 and here f(x) is -1
<u>Putting</u><u> </u><u>f</u><u>(</u><u>x</u><u>)</u><u> </u><u>=</u><u> </u><u>-</u><u>1</u>.
For g(x) put as -1
<u>Last</u><u> </u><u>step</u><u>,</u><u> </u>
<u>So</u><u>,</u><u> </u><u>option</u><u> </u><u>(</u><u> </u><u>a</u><u>)</u><u> </u><u>is</u><u> </u><u>correct</u><u> </u>
edi wow
bwiset ka hahaha
Now
d= (3-10h)/f
-2
The answer is C. -336
All you have to do is 25 - 39 = -14 x 24 = -336
Hope this helps :)